ANALISIS TINGKAT EFISIENSI PUSKESMAS KOTA MEDAN DENGAN MODEL DEA - Indah Simamora; Ferdinand Sinuhaji (JURNAL CURERE, 2021)
The research objective was to measure the relative efficiency value of Medan city health centers using the DEA model and determine the calculation of input and output targets to increase the efficiency value of the inefficient DMU. The research subjects were patients at the Medan City Health Center. The data collection technique was carried out using BPS secondary data. The discussion in this study shows that inefficient health centers, namely Health Center of Medan Tuntungan, Health Center of Medan Johor , Health Center of Medan Polonia, Health Center of Medan Baru, Health Center of Medan Barat, and inefficient target improvements refer to CRS for non-optimal variables. It can be achieved by increasing the number of nurses, increasing the number of midwives, increasing the number of diarrhea patients, adding number of baby births and carried out through socialization activities regarding the relevant puskesmas facilities The inefficient improvements to the Puskesmas repairs were 0.71966, 0.7946, 0.938, 1.1356 and 0.99659.